Model of decision support of selection project team - Юрий Николаевич Харитонов (Tehnologìčnij Audit ta Rezervi Virobnictva, 2013)
One of the main problems for the energy sector in Ukraine is the problem of modernization and reconstruction of municipal heat supply systems (HSS). Among the most common problems associated with heat supply systems of municipalities of Ukraine, which  substantially  determine the relevance of  the formation and implementation of projects and programs of reconstruction can be determined, the following ones: technical - technological, ecological, social and economic. At the same time, as practical experience shows the effectiveness of the project implementation significantly depends on the project team, that makes the solution of the problem of the team’s reasonable choice actual and having important practical significance. At this article the model of decision support system for selecting a project team was developed for the first time. Many restrictions, formed to meet the requirements of the customer, institutional authorities, classification criteria of the project, possible propositions from the project team, as well as many other criteria were put into the base of the system. Is model allows to formalize the process of selection the team, automate the decision making process when selecting the project team for reconstruction the HSS, as well as significantly reduce the risk of making incorrect decisions.